THE ROLE OF PROFITABILITY IN THE RELATIONSHIP BETWEEN ENVIRONMENTAL DISCLOSURE AND FIRM VALUE - Galuh Sekar Megananda; Andri Prastiwi (AKUMULASI: Indonesian Journal of Applied Accounting and Finance, 2022)
This study aimed to examine the consistency of the effects of environmental disclosure on firm value and investigate profitability as a moderating variable. The samples in this study were companies that won the Sustainability Reporting Award (SRA) and the Asia Sustainability Reporting Rating (ASRAT) presented by the National Center for Sustainability Reporting (NCSR) in the 2014-2020 period. A total of 82 companies were sampled. This study used secondary data taken from company databases and the Indonesia Stock Exchange (IDX)/Bursa Efek Indonesia (BEI). The multiple regression equation model was analyzed using IBM SPSS 20 software. The results showed that environmental disclosure negatively and significantly affected firm value. Furthermore, research documented that environmental disclosure had a positive and significant effect on firm value when profits were high. These findings have provided evidence that the differences in results on the relationship between environmental disclosure and firm value are due to a conditional factor, namely profitability. Based on the stakeholder theory, fulfilling stakeholder interests has a positive effect if the company has good financial performance. Meanwhile, based on the signaling theory, financial information is required for non-financial information to be effective.